EXPLORING ACCOUNTANTS' VIEWS ON THE FUTURE OF THE PROFESSION IN THE ERA OF ARTIFICIAL INTELLIGENCE - zalni; Hempry Putuhena; M. Rifkhi Fauzan S (INQUISITIVE : International Journal of Economic, 2025)
Goldman Sachs has projected that Artificial Intelligence (AI) may potentially replace the equivalent of 300 million full-time jobs worldwide, as many occupational tasks and functions can be automated. AI technologies are particularly useful in accounting-related work, with platforms such as QuickBooks, Xero, Sage Intacct, BlackLine, and AuditBoard already widely applied. The purpose of this study is to examine the attitudes, knowledge, expectations, and concerns of respondents regarding the future of the accounting profession. Adopting a quantitative descriptive approach, this research uses data quality tests, variable descriptions, and crosstab analyses, with data collection through online questionnaires. The findings indicate generally positive perceptions toward the importance of skills development, training, and readiness to adapt to AI technologies, which are believed to enhance the efficiency and quality of accounting work. However, a portion of respondents expressed concern over ethical implications and the potential replacement of certain routine tasks.